Exploring Fine Motor Skills Research in Early Childhood: Trends and Performance through Bibliometric Analysis - Ahmad Tazli, Uzzairah Nabila; Nik Yaacob, Nik Rosila; S. Pd. I, Rahmawati (Southeast Asia Early Childhood Journal, 2026)
Fine motor skills are the skills of using small muscles that children need to master as preparation for school. This skill facilitates the mastery of basic skills since preschool, namely reading, writing, counting, and reasoning. The purpose of this paper is to analyse the scientific production on Fine Motor Skills in journals indexed in Scopus. The data is retrieved from the database between 2020 and 2025. Data collection was conducted in August 2025, which identified 303 related research articles about fine motor skills among early childhood. The results obtained by bibliometric analysis from Scopus database and VOSViewer identify the key trends, influential authors and subject areas regarding fine motor skills in early childhood. These research findings demonstrate a significant rise in publications and citations. The analysis also highlights the United States at the leading country of research output, including articles, publications and citations. The obtained results provide fundamental knowledge into research on fine motor skills among children while addressing potential future research.